Customer satisfaction analysis and its impact on customer loyalty delivery services reviewed from service quality and price - Djan, Ismulyana; Adawiyyah, Siti Rubbiah (Technium Social Sciences Journal, 2021)
The purpose of this research is to find out how the effect of service quality and price on customer satisfaction and the impact on customer loyalty on customer delivery services J&T Express Bogor. This research uses quantitative approach by collecting data through survey method. The population in this study was users of J&T Express delivery services in Bogor. Sampling techniques using purposive sampling method with the criteria of users of J&T Express delivery services in Bogor who are able to perform or feel the services performed by J&T Express Bogor. The sample of 178 respondents using the technique used questionnaires. The data analysis techniques in this research use structural equation model analysis techniques. The results of this research showed that: (1) service quality has a positive and significant effect on customer satisfaction with a critical ratio of 10,967 with a large influence of 0.920. (2) Price has no effect and is significant to customer satisfaction because it has a critical ratio value of only 1,121. (3) Service Quality has no effect and is significant to customer loyalty because it has a critical ratio value of only 0.225. (4) price positively and significantly affect customer loyalty with critical ratio value of 2,454 with a large influence of 0.099. (5) customer satisfaction has a positive and significant effect on customer loyalty with a critical ratio of 6,138 with a large influence of 0.968. (6) customer satisfaction does not mediate between service quality and customer loyalty because it has a calculated t value of 0.660598. And (7) customer satisfaction does not mediate between service quality and customer loyalty because it has a calculated t value of 0.067883.